Closing the loop: a 10-year experience with routine outcome measurements to improve treatment in hand surgery. Issue 6 (28th June 2021) - Feitz, Reinier; van Kooij, Yara E.; ter Stege, Marloes H. P.; van der Oest, Mark J. W.; Souer, J. Sebastiaan; Wouters, Robbert M.; Slijper, Harm P.; Selles, Ruud W.; Hovius, Steven E. R.; ,
Abstract : Routine outcome measurements as a critical prerequisite of value-based healthcare have received considerable attention recently. There has been less attention for the last step in value-based healthcare where measurement of outcomes also leads to improvement in the quality of care. This is probably not without reason, since the last part of the learning cycle: 'Closing the loop', seems the hardest to implement. The journey from measuring outcomes to changing daily care can be troublesome. As early adopters of value-based healthcare, we would like to share our 10 years of experience in this journey. Examples of feedback loops are shown based on outcome measurements implemented to improve our daily care process as a focused hand surgery and hand therapy clinic. Feedback loops can be used to improve shared decision making, to monitor or predict treatment progression over time, for extreme value detection, improve journal clubs, and surgeon evaluation. Our goal as surgeons to improve treatment should not stop at the act of implementing routine outcome measurements. We should implement routine analysis and routine feedback loops, because real-time performance feedback can accelerate our learning cycle. Cite this article: EFORT Open Rev 2021;6:439-450. DOI: 10.1302/2058-5241.6.210012